ISLAM NORMATIF DAN ISLAM HISTORIS - Rendy Saputra; Ris’an Rusli; Anisatul Mardiah; Ahmad Wahyu Hidayat (Fakultas Ushuluddin dan Pemikiran Islam Universitas Islam Negeri Raden Fatah Palembang, 2021)
This paper focuses on normative and historical Islamic studies. This research uses descriptive analytic method. Islam is the last religion and the guidelines of the Islamic religion come from revelations or holy books that were revealed to the Prophet Muhammad SAW by Allah SWT through the angel Gabriel. The emergence of Islam to bring peace to mankind. Normative/theological Islam understands the meaning of religion as an attempt to build an understanding of religion based on the construction of Divine Science whose source is belief and judges that belief is the most correct of all. While historical Islam is a scientific discipline that discusses an event based on who the perpetrator, background, object, time and place of occurrence are. In this case, each event can be known how, when, where, why and who in the incident. All of these elements are then constructed into a unit called history. When associated with Islamic studies, history can be interpreted with an analysis of all events related to Islam since the era of the Prophet Muhammad SAW until now, because Islam cannot be separated from its history. Based on Amin Abdullah's view that the relationship between the two is like a coin with two different faces. Where the two different faces cannot be separated. The existing relationship is not merely a discussion alone, but both are built together and complement each other so that a very close and compact relationship is established. The meaning of religious and deepest morality still exists, takes precedence and works hand in hand in understanding human diversity. Therefore, it will not be possible to escape the traps and shackles of time and space and support each other.